The determinant factors of school organizational change in Madura, East Java, Indonesia - Mochammad Rozikin; Abd. Qadir Muslim; Bayu Indra Pratama (Institute of Advanced Engineering and Science, 2021)
Organizational change is a phenomenon that must be faced and carried out by every individual in the organization to achieve organizational goals. Embodiments of organizational change often occur not because it suits the needs of the organization but because of personal interests and power. This study aimed to determine the main factors that can create change, namely the relationship of leadership and political pressure of school principals that influence organizational change in the Public Secondary School in Madura, East Java, Indonesia. This research used a quantitative approach to survey methods. Based on the achievement of its objectives, this study included causal explanation research, the analysis of this study using Structural Equation Modeling (SEM) and a sample of about 650 people collected from 1000 respondents taken from 130 schools through probability sampling techniques using AMOS software. The results showed that the leadership and political pressure of regional heads were the main factors of organizational change at SMPN (Public Secondary School) in Madura, East Java. Organizational Change depends very much on the role of the political pressure of the regional head through education policy, as well as the role of the principal's leadership in running the wheels of the organization so that the school's goals can be achieved. This study also showed that the principal's leadership as an intermediary variable from political pressure shows no influence because the political pressure of the regional head is directly related to organizational change.